Real-world rates, predictors, and associated costs of hypoglycemia among patients with type 2 diabetes mellitus treated with insulin glargine: results of a pooled analysis of six retrospective observational studies. (2nd August 2013) - Xie, Lin; Wei, Wenhui; Pan, Chunshen; Baser, Onur
Abstract: Objective: To evaluate the real-world rates of hypoglycemia and related costs among patients with type 2 diabetes mellitus (T2DM) who initiated insulin glargine with either a disposable pen or vial-and-syringe. Methods: Pooled data were evaluated from six previously published, retrospective, observational studies using US health plan insurance claims databases to investigate adults with T2DM who initiated insulin glargine. The current study evaluated baseline characteristics, hypoglycemic events, and costs during the 6 months prior to and 12 months following insulin glargine initiation. Comparisons were made between patients initiating treatment with a disposable pen (GLA-P) and vial-and-syringe (GLA-V). Multivariate analyses using baseline characteristics as covariates determined predictors of hypoglycemia after initiating insulin glargine. Results: This study included 23, 098 patients (GLA-P: 14, 911; GLA-V: 8187). Overall annual prevalence of hypoglycemia was low (6.3% overall, 2.2% related to hospital admission or emergency department visit). Prevalence was significantly lower with GLA-P (5.5% vs 7.7%; p  < 0.0001). Furthermore, average glycated hemoglobin HbA1c reduction was higher with GLA-P (−1.22% vs −0.86%; p  = 0.0012). The average annual hypoglycemia-related cost associated with initiating insulin glargine was $293, with GLA-P being 46% lower than GLA-V ($225 vs $417; p  = 0.001). Patients who had already developed microvascular complications at the time of initiating insulin therapy were at higher risk for developing hypoglycemia. Limitations: This study is limited by the use of retrospective data and ICD-9-CM codes, which are subject to coding error. In addition, this pooled analysis used unmatched cohorts, with multivariate regression analyses employed to adjust for between-group differences. Finally, results describe a managed care sample and cannot be generalized to all patients with T2DM. Conclusions: Patients with T2DM initiating insulin glargine treatment showed low rates of hypoglycemia, especially when using a disposable pen device. Hypoglycemia-related costs were low, contributing a very small proportion to overall diabetes-related healthcare costs.